Cluster policy, innovation, and firm productivity: An econometric assessment of the Flemish Spearhead Cluster Program - Pierluigi Angelino; Dirk Czarnitzki; Astrid Volckaert (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
The Flemish government launched its Spearhead Cluster (SHC) policy in 2017. The aim is to boost strategic sectors by setting up cluster initiatives which coordinate collaborative R&D initiatives. In this paper, we analyze whether becoming a member of such a cluster initiative has an impact on the Total Factor Productivity (TFP) of the firm. We exploit firm-level data between 2013 and 2020 to estimate TFP and apply a difference-in-differences approach to assess the programs' treatment effects. We find that becoming a member of a cluster has an average positive impact on firmlevel TFP of between 1 to 4.4 percent, depending on the econometric specification. These results are the first to provide an insight into the impact of the Flemish SHC policy on productivity.
Keywords: D24; L25; L52; L53; O25; O38; 330; cluster associations; cluster policy; innovation policy; total factor productivity; conditional difference-in-difference